INTERPRETATION OF GRAVITY DATA TO IDENTIFICATE BANDUNG BASIN SUBSURFACE - DIANA SAFITRI (NIM : 20216032),
Geophysical research had been done using gravity methods in the Bandung basin area, West Java, which was carried out in two periods. This study aims to determine the shape of the subsurface structure of the Bandung basin. Gravity measurements were carried out on 210 stations using the Lacoste & Romberg G-928 gravimeter with a distance of Ã‚Â± 2000 m which stretched from north to south. Data reduction was performed on corrections of gravity method data so that the Complete Bouguer Anomaly (CBA) value was obtained at 181.48 mGal to 252.52 mGal. Separation of regional and residual anomalies was done by utilizing several filters including butterworth filters, upward continuation, and moving averages. Fast Fourier Transform was used to convert spatial data into the frequency domain to obtain a cut off wave number (k cut off) of 0.16 km-1. Spectrum analysis shows the depth of the geological structure of the study area from north to south is at a depth of more than 1600 m for deep anomalies and less than 1600 m for shallow depth anomalies. Geological information on the study area is needed for data interpretation. Furthermore, forward modeling was carried out to obtain 2D contrast density models in the study area. This forward modelling was done to get the basement shape below the surface of the study area.